Design and Build Android-Based Applications of Software Development Projects Effort and Cost Estimation - Juliana Kristi; Renny Sari Dewi (School of Industrial and System Engineering, Telkom University, 2021)
Prediction of software business and costs needs to be done carefully and clearly measured so that thesuccess of a software development project can be achieved. There are 2 methods that are commonly usedto estimate software development efforts and costs, such Function Points (FP) and Use Case Points. Therewere 4 stages of the research carried out: literature study, needs analysis, design, and implementation(application development to testing). Analysis and application design using the Signavio tools. Meanwhile,the author uses open source rapid application development (RAD), called Kodular. The trial phase iscarried out by verifying manual calculations whose projects have been completed. The result of thisresearch is the creation of an Android-based application that can be used to accelerate business players inthe software development sector in the process of estimating product prices. This research has limitation isnot tested the validity of the soft development project which is still in the planning stage.